Economic study of Binadhan-22 production in some selected areas of Bangladesh - Sarkar, M M A; Rahman, M H; Haque, M R; Islam, S (Bangladesh Journal of Nuclear Agriculture, 2024)
This study was conducted in four districts of Bangladesh, namely Mymensingh, Bogura, Naogaon and Rangpur to estimate the profitability and factors affecting gross return of the variety. This study was based on primary data which were collected from 200 Binadhan-22 growing farmers. In the sampled areas data were collected through pre-designed interview schedule from January-February, 2023. Tabular, descriptive statistics and Cobb-Douglas production function model were used to fulfill the objectives. It was found that Binadhan-22 production is profitable. The average net return per hectare was Tk. 28876. The net return was highest in Rangpur (Tk. 32480/ha) followed by Naogaon (Tk. 28554/ha), Mymensingh (Tk. 27331/ha) and Bogura (Tk. 27139/ha), respectively. Benefit cost ratio was estimated at 1.39 and 2.04 on full cost and variable cost basis. Cobb-Douglas production function was chosen to determine the factor affecting gross return of Binadhan-22 production. All of the factors namely, human labour cost, power tiller cost, seed cost, fertilizer cost, irrigation cost, insecticides cost were statistically significant and positive. The regression coefficients for farming experience and agricultural training under all areas had negative but significant relationship at 5% and 10% level, respectively. The regression coefficient of age was positive and significant at 10% level. Under all areas, the regression coefficients of education and farm size were positive but not significant. Farmers faced some constraints in cultivating of the variety. The first ranked constraint was lack of availability of seeds (93%). Other constraints were lack of training (61%), lack of capital (38%) and lack of technical know-how (16%). In addition to helping farmers use a better combination of inputs that will create higher productivity and return, effective extension services may also assist farmers in cultivating rice in a way that will contribute to food security and self-sufficiency. Bangladesh J. Nuclear Agric, 38(1): 81-91, 2024